2021
DOI: 10.1515/jbcpp-2020-0347
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use and clinical leukoplakia lesions among south Indian tribes

Abstract: Objectives Leukoplakia is a white mucosal thickening and perhaps undermining change in the oral mucosa transcendently found in tobacco users. Since the tobacco utilization is extensively higher with the indigenous groups in the Asia Pacific locale, the current examination implicated the prevalence of tobacco consumption and leukoplakial lesions and the relationship between the two. Methods This cross-sectional study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…11 Another study revealed that clinical oral leukoplakia was diagnosed in 27 (8.5%) of the 317 people who were screened at the placement site of smokeless tobacco. 12 Another research revealed throughout the complete range of tobacco products used by American adolescents, correlated with a high risk mental health problems concerns. 13 Furthermore, in the United States, 16% of White high school adolescents were currently using Smokeless tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…11 Another study revealed that clinical oral leukoplakia was diagnosed in 27 (8.5%) of the 317 people who were screened at the placement site of smokeless tobacco. 12 Another research revealed throughout the complete range of tobacco products used by American adolescents, correlated with a high risk mental health problems concerns. 13 Furthermore, in the United States, 16% of White high school adolescents were currently using Smokeless tobacco.…”
Section: Introductionmentioning
confidence: 99%